2019
DOI: 10.3847/1538-4357/ab40a5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Studies from Tomographic Weak Lensing Peak Abundances and Impacts of Photo-z Errors

Abstract: Weak lensing peak abundance analyses have been applied in different surveys and demonstrated to be a powerful statistics in extracting cosmological information complementary to cosmic shear two-point correlation studies. Future large surveys with high number densities of galaxies enable tomographic peak analyses. Focusing on high peaks, we investigate quantitatively how the tomographic redshift binning can enhance the cosmological gains. We also perform detailed studies about the degradation of cosmological in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
5
0
1
Order By: Relevance
“…The largest gain is observed when going from 1 (no tomography) to 2 slices, and does not evolve any more above ∼5 slices. This is in good agreement with results from Yuan et al (2019) who found for a Euclid-like weak-lensing peak analysis that the constraints on Ω m and σ 8 are only marginally improved when using 8 tomographic slices compared to 4. This is no longer the case when we additionally include cross-M ap terms.…”
Section: D M Ap Tomographic Forecastssupporting
confidence: 91%
See 1 more Smart Citation
“…The largest gain is observed when going from 1 (no tomography) to 2 slices, and does not evolve any more above ∼5 slices. This is in good agreement with results from Yuan et al (2019) who found for a Euclid-like weak-lensing peak analysis that the constraints on Ω m and σ 8 are only marginally improved when using 8 tomographic slices compared to 4. This is no longer the case when we additionally include cross-M ap terms.…”
Section: D M Ap Tomographic Forecastssupporting
confidence: 91%
“…Two-point statistics fail to capture this non-Gaussian information and thus yield an incomplete description of the matter distribution at low redshift. To close this gap, the community has recently started to explore non-Gaussian cosmic shear estimators: for example weak-lensing peaks (e.g., Kruse & Schneider 1999, 2000Dietrich & Hartlap 2010;Kratochvil et al 2010;Fan et al 2010;Yang et al 2011;Maturi et al 2011;Hamana et al 2012;Hilbert et al 2012;Marian et al 2012Marian et al , 2013Shan et al 2014Shan et al , 2018Lin & Kilbinger 2015;Martinet et al 2015Martinet et al , 2018Liu et al 2015a,b;Kacprzak et al 2016;Petri et al 2016;Zorrilla Matilla et al 2016;Giocoli et al 2018;Peel et al 2018;Davies et al 2019;Fong et al 2019;Li et al 2019;Weiss et al 2019;Yuan et al 2019;Coulton et al 2020;Ajani et al 2020;Zürcher et al 2021), Minkowski functionals (e.g., Kratochvil et al 2012;Petri et al 2015;Vicinanza et al 2019;Parroni et al 2020;Zürcher et al 2021), higher-order moments (e.g., Van Waerbeke et al 2013;Petri et al 2015;Peel et al 2018;Vicinanza et al 2018;…”
Section: Introductionmentioning
confidence: 99%
“…weak-lensing peaks (e.g. Kruse & Schneider 1999, 2000Dietrich & Hartlap 2010;Kratochvil et al 2010;Fan et al 2010;Yang et al 2011;Maturi et al 2011;Hamana et al 2012;Hilbert et al 2012;Marian et al 2012Marian et al , 2013Shan et al 2014;Lin & Kilbinger 2015;Martinet et al 2015;Liu et al 2015a,b;Kacprzak et al 2016;Petri et al 2016;Zorrilla Matilla et al 2016;Shan et al 2018;Martinet et al 2018;Giocoli et al 2018;Peel et al 2018;Davies et al 2019;Fong et al 2019;Li et al 2019;Weiss et al 2019;Yuan et al 2019;Coulton et al 2020;Ajani et al 2020;Zürcher et al 2020), Minkowski functionals (e.g. Kratochvil et al 2012;Petri et al 2015;Vicinanza et al 2019;Parroni et al 2020;Zürcher et al 2020), higher-order moments (e.g.…”
Section: Introductionunclassified
“…In Yuan et al (2019), we investigate theoretically the gain from tomographic high peak analyses. In the case with the galaxy number density g ∼ 40 arcmin −2 and the redshift distribution similar to that expected from LSST, 2 to 4 tomographic bins are the optimal.…”
Section: The Hsc-ssp Shear Samplementioning
confidence: 99%
“…Similarly to cosmic shear correlations, theoretical studies have shown that adding redshift information in peak analyses, i.e., tomographic peak statistics, can effectively enhance the cosmological gains in comparison with that from non-tomographic, or 2D peak statistics (Yang et al 2011;Martinet et al 2015;Petri et al 2016;Abruzzo & Haiman 2019;Yuan et al 2019). Limited by the number density of galaxies in the shear samples from the current surveys, however, most of the observational peak studies to date are 2D without tomography.…”
Section: Introductionmentioning
confidence: 98%